Tolerance of rats to hyperoxia. Lung antioxidant enzyme gene expression. - Clerch, L B (1993)
Tolerance to hyperoxia usually requires an increase of lung antioxidant enzyme (AOE) activity. We used rats with different degrees of tolerance to > 95% O2 to evaluate the importance of individual AOEs for tolerance; we also explored the regulation of AOE gene expression. During exposure of adult rats to > 95% O2, lung manganese superoxide dismutase (MnSOD) activity fell approximately 50% despite a threefold increase of MnSOD mRNA concentration; addition of a reducing agent to lung extracts from O2-exposed rats partially restored MnSOD activity. Endotoxin induced tolerance to O2 (a) without elevating Cu,Zn superoxide dismutase activity, (b) with increases of catalase and glutathione peroxidase (GP) activity of the same magnitude as occurred in O2-saline rats, but (c) with MnSOD activity 1.5-1.9-fold higher than in air-saline rats and 1.4-3.6-fold higher than in O2-saline rats. Endotoxin elevated the concentration of MnSOD and GP mRNAs without increasing their stability. O2 elevated MnSOD mRNA concentration, and increased its stability. O2 plus endotoxin increased the concentration and stability of MnSOD, catalase, and GP mRNAs. These data suggest that in adult rats tolerance to hyperoxia requires increased MnSOD activity; the data show gene expression and regulation vary among the AOEs, and that increased stability of the AOEs' mRNAs plays an important role in AOE gene expression and in tolerance to hyperoxia.